PENGARUH ON THE JOB TRAINING DAN JOB DESCRIPTION TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BANK SYARIAH NASIONAL KANTOR CABANG SURABAYA - Fitriah; Ony Kurniawati; Mira Gayatri Kartika; Dedy Kunhadi; Alfiyatussholichah (STIE Mahardhika, 2026)
This study aims to determine the effect of on the job training and job descriptions on employee productivity at PT. Bank Syariah Nasional, Surabaya Branch Office. This study used a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to 78 respondents, who were employees of the company. The data obtained were then analyzed using multiple linear regression analysis techniques with the aid of SPSS statistical software. The results showed that on the job training significantly influenced employee productivity. This suggests that training conducted directly in the workplace can improve employees' abilities and understanding of the tasks they perform. Furthermore, job descriptions also significantly influenced employee productivity. Clarity regarding the division of tasks and responsibilities helps employees carry out their work more focused and effectively. Simultaneously, on the job training and job descriptions were proven to have a significant impact on employee productivity. The analysis also showed that these two variables explained a significant portion of the variation in employee productivity, with the remainder influenced by factors outside the research model. The findings of this study indicate that the implementation of a sound job training program and the development of clear job descriptions are important factors in efforts to increase employee productivity.